The Influence Of Prices And Promotions On Purchasing Decisions At PT. Madju Abadi Sejahtera West Jakarta City - Nuraeni, Erni; Nani, Nani (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2025)
This research aims to determine the influence of price and promotion on purchasing decisions at PT. Madju Abadi Sejahtera, West Jakarta City. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research show that price has a significant effect on purchasing decisions by 62.7%. Hypothesis testing shows that t count > t table or (5.548 > 1.993). Promotion has a significant effect on purchasing decisions by 59.9%, hypothesis testing obtained t count > t table or (5.016 > 1.993). Price and promotion simultaneously have a significant effect on purchasing decisions with the regression equation Y = 8.828 + 0.370X1 + 0.511X2 and an influence contribution of 72.5%, the hypothesis test obtained calculated F > F table or (88.505 > 3.13).